Descriptions of sham acupuncture in randomised controlled trials: a critical review of the literature - Yixuan Xie; Xiaoyu Liu; Tinglan Liu; Chiyun Sun; Zeyin Xin; Yuzhi Hu; Yue Wang; Cheng Zhang; Shiyan Yan (BMC, 2023)
Abstract Background Sham acupuncture is usually used to assess the specific effects of acupuncture. However, the reporting quality of sham acupuncture remains unclear despite its critical importance in understanding and analyzing the effects of acupuncture. This paper presents a literature review aimed at assessing the quality of reporting of sham acupuncture in randomized controlled trials (RCTs) based on STRICTA 2010 and TIDieR-Placebo. Methods Three electronic English-language databases (PubMed, MEDLINE and Embase) were searched from inception to March 7, 2022, and RCTs of sham acupuncture were identified. The reporting quality of sham acupuncture was assessed in accordance with the items recommended in STRICTA 2010 and TIDieR-Placebo. The reporting quality of other items related to sham acupuncture apart from items from these two checklists was also captured to further assess the reporting quality of sham acupuncture. Results A total of 609 eligible studies were included. For all of the items recommended in STRICTA 2010 and TIDieR-Placebo, 100% of the studies reported a brief name that described the sham acupuncture, 93.9% studies reported the needle type, and 90.0% reported the names of the points used. Other items for which the reporting rates were above 50% included the number, frequency and duration of treatment sessions; needle retention time; and number of needle insertions per subject per session. Overall, 49.4% of the studies revealed the rationale why sham acupuncture was chosen, 39.7% of the studies involving insertion processes reported the depth of insertion, and 37.9% of the studies reported the needle manufacturer. Other items for which the reporting rates were below 30% included practitioner-related information, response sought, evaluation of blinding, intervention mode and environment, assisting tools, and the extent to which the treatment was varied. The items "Modifications", "How well (planned)" and "How well (actual)" were not reported in any of the analyzed studies. Conclusions The overall reporting quality of sham acupuncture in RCTs was suboptimal. Although STRICTA 2010 and TIDieR-Placebo could be beneficial for describing sham acupuncture, neither can offer recommendations specifically for sham acupuncture. There is thus an urgent need to develop specialized guidelines for reporting sham acupuncture in clinical trials.